2011
DOI: 10.1175/2010mwr3574.1
|View full text |Cite
|
Sign up to set email alerts
|

Lightning Activity in a Hail-Producing Storm Observed with Phased-Array Radar

Abstract: This study examined lightning activity relative to the rapidly evolving kinematics of a hail-producing storm on 15 August 2006. Data were provided by the National Weather Radar Testbed Phased-Array Radar, the Oklahoma Lightning Mapping Array, and the National Lightning Detection Network.This analysis is the first to compare the electrical characteristics of a hail-producing storm with the reflectivity and radial velocity structure at temporal resolutions of less than 1 min. Total flash rates increased to appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
73
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 69 publications
5
73
0
Order By: Relevance
“…Ice crystals and graupel/small hail contribute to electrification of thunderstorms and their typical fall speeds have been found to be ≤10 m s −1 (e.g., Dye et al 1983, Dye et al 1986, Musil et al 1986, Musil and Smith 1989. The literature also shows that lightning propagation typically avoids regions of peak updraft speed and intense updraft volume due to lower concentrations of precipitation size ice and a lack of available charge (e.g., Wiens et al 2005, Payne et al 2010, Emersic et al 2011, Calhoun et al 2013, Kozlowski and Carey 2014. These regions are referred to as "lightning holes."…”
Section: Discussion a The Importance Of Peak Updraft Speed And 10 M mentioning
confidence: 99%
“…Ice crystals and graupel/small hail contribute to electrification of thunderstorms and their typical fall speeds have been found to be ≤10 m s −1 (e.g., Dye et al 1983, Dye et al 1986, Musil et al 1986, Musil and Smith 1989. The literature also shows that lightning propagation typically avoids regions of peak updraft speed and intense updraft volume due to lower concentrations of precipitation size ice and a lack of available charge (e.g., Wiens et al 2005, Payne et al 2010, Emersic et al 2011, Calhoun et al 2013, Kozlowski and Carey 2014. These regions are referred to as "lightning holes."…”
Section: Discussion a The Importance Of Peak Updraft Speed And 10 M mentioning
confidence: 99%
“…This is despite the fact that thunderstorm charging can be locally reduced in regions of wet hail growth (Saunders and Brooks 1992;Pereyra et al 2000;Emersic et al 2011), likely because of the reduced number of rebounding collisions between water-coated graupel and ice crystals. Lightning flash rate also has been found to be correlated with updraft strength, updraft volume, and graupel mass (e.g., Carey and Rutledge 1996;Wiens et al 2005;Tessendorf et al 2007;Deierling and Petersen 2008;Deierling et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Severe storms present a normal charge structure in the initial stages, and then the inverted charge structure appears as the storm evolves . Zheng et al (2009) and Emersic et al (2011) found that, during the stage of hail-fall, the charge structure of a storm is inverted and then returns to normal after the hail-fall has ended. The vertical charge structure initially displays a normal tripole structure; however, as the hail begins to fall, a negative charge region is found above a deep central positive charge region.…”
Section: Introductionmentioning
confidence: 99%